Quantitative Uncertainty polycyclic aromatic hydrocarbon (PAH) metadata, 2006-2008. ... - Thackray, Colin (NSF Arctic Data Center, 2016)
We quantitatively examine the relative importance of uncertainty in emissions and physicochemical properties (including reaction rate constants) to Northern Hemisphere (NH) and Arctic polycyclic aromatic hydrocarbon (PAH) concentrations, using a computationally efficient numerical uncertainty technique applied to the global-scale chemical transport model GEOS-Chem. Using polynomial chaos (PC) methods, we propagate uncertainties in physicochemical properties and emissions for the PAHs benzo[a]pyrene, pyrene and phenanthrene to simulated spatially resolved concentration uncertainties. We find that the leading contributors to parametric uncertainty in simulated concentrations are the black carbon-air partition coefficient and oxidation rate constant for benzo[a]pyrene, and the oxidation rate constants for phenanthrene and pyrene. NH geometric average concentrations are more sensitive to uncertainty in the atmospheric lifetime than to emissions rate. We use the PC expansions and measurement data to constrain ...